Analysing the Effects of Waste, Changes in Land Use, and Population Density on Air Pollution in Greater Jakarta, Indonesia through the Use of Google Earth Engine - Umwanzisiwemuremyi, Oscar; Abidin, Zaenal; Setiawan, Yudi (Amcolabora, 2026)
Air pollution has become a challenge in recent years due to the rising of atmospheric contaminants. The increase in anthropogenic activities has led to emissions, accelerating this issue and along with environmental degradation and health problems. Researchers have noted driving factors such as energy generation, industrial operations, volcanic eruptions, and wildfires. Consequently, population density drives land use, land cover (LULC) alterations, and waste generation. Nevertheless, these factors are often overlooked when considering their contribution on emissions, which we strive to emphasize in this study. We have examined the impacts of waste, LULC, and population density on sulphur dioxide SO2, carbon monoxide (CO), nitrous dioxide (NO2), and formaldehyde (CH2O) emissions in Jakarta and its auxiliary regions in Indonesia. We gathered data from the Sentinel-2, Sentinel-5, and Copernicus, as well as waste datasets, from 2019 through 2023. Then, we analysed them via the Google Earth Engine (GEE), Excel, ArcGIS 10.8, and Minitab. Our findings indicated that population density, coupled with waste and LULC changes correlated with elevated emissions, except for SO2, which showed no such relation. This study brings out the persuasive necessity for feasible waste disposal, urban greening, reforestation, and family planning to mitigate air quality deterioration and its adverse consequences.